Structured Play Program Supports Gross Motor Development in Early Childhood: Program Bermain Terstruktur Mendukung Perkembangan Motorik Kasar pada Masa Kanak-kanak Awal - Aisyha Nur Aini; Agus Salim (Academia Open, 2025)
General Background Early childhood education prioritizes holistic child development, including physical and gross motor abilities that support children’s daily activities and learning readiness. Specific Background Play-based learning is widely implemented in kindergarten settings, yet the organization of structured play programs to systematically stimulate large muscle coordination remains varied across schools. Knowledge Gap Limited empirical descriptions explain how daily play activities are implemented and what practical barriers teachers face in facilitating gross motor stimulation in real classroom contexts. Aims This study analyzes the implementation of a structured play activity program and identifies challenges experienced by teachers in developing gross motor skills among children at TK Aisyiyah Bustanul Athfal III Candi. Results Using a descriptive qualitative approach with observation, interviews, and documentation, findings show that activities such as running and jumping along lines, throwing and catching balls, kicking to goals, balancing objects, group exercises, and modified games foster muscle strength, balance, agility, coordination, and concentration, while constraints include limited space and varying child readiness, addressed through game modification and small-group strategies. Novelty The study provides contextual evidence of daily structured play practices aligned with national developmental indicators in one kindergarten setting. Implications The results suggest that consistent and well-managed play programs with adaptive strategies can support gross motor stimulation in early childhood classrooms. Keywords: Structured Play, Gross Motor Skills, Early Childhood Education, Kindergarten Program, Physical Development Key Findings Highlights: Daily movement sessions build strength, balance, agility, coordination, and focus Game modification and grouping address limited facilities and space constraints Teacher facilitation shapes children’s active participation during learning routines